Ebola and art - Schoenhagen, Paul; Weiner, Mia (Cardiovascular Diagnosis and Therapy, 2014)
The cover image of the current issue of our journal shows an embroidered image of the Ebola virus. The complex shape of viruses has inspired artist to render these microscopic sized particles (1,2). In a submission to our Art-and-Medicine series in 2013, which includes the cover image of this issue, artist Mia Weiner described her interest in the correlation between working in fibers and the microscopic world (1). She described that by embroidering images of Ebola, the virus becomes an object of beauty, with its destructive nature and danger to the human body hidden.